2005
DOI: 10.1271/bbb.69.137
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Lewis a Epitope inN-Glycans of a Glycoallergen, Jun a 1, from Mountain Cedar (Juniperus ashei) Pollen

Abstract: We have determined the structures of N-glycans linked to major allergens in the mountain cedar (Juniperus ashei) pollen, Jun a 1. First, two kinds of the pollen glycoallergen (Jun a 1-A and Jun a 1-B) were purified from partially purified Jun a 1 by cation exchange chromatography. The N-glycans were liberated by hydrazinolysis from the two glycoallergens and the resulting sugar chains were N-acetylated and then coupled with 2-aminopyridine. Three pyridylaminated sugar chains were purified by reversed-phase HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Given the complex architecture of the GALT1 protein, it is also possible that structural constraints permit the enzyme to act only on a small subset of endogenous glycoproteins. This is substantiated by the fact that until now only few purified plant glycoproteins have been found to carry Le a epitopes (Fitchette-Lainé et al, 1997;Melo et al, 1997;Kimura et al, 2005).…”
Section: Le a : A Tissue-specific Structural Element Of Complex Arabimentioning
confidence: 98%
“…Given the complex architecture of the GALT1 protein, it is also possible that structural constraints permit the enzyme to act only on a small subset of endogenous glycoproteins. This is substantiated by the fact that until now only few purified plant glycoproteins have been found to carry Le a epitopes (Fitchette-Lainé et al, 1997;Melo et al, 1997;Kimura et al, 2005).…”
Section: Le a : A Tissue-specific Structural Element Of Complex Arabimentioning
confidence: 98%
“…The very large Lewis a type structures are rarely found on soluble allergens and are currently thought to play only a minor, if any, role in IgE binding even though many plant foods (apple, banana, celery, onion, orange, pear, and strawberry) contain large amounts of these near-mammalian N-glycans [20]. The cedar pollen allergens Cry j 1 and Jun a 1 are the only allergens known to contain Lewis a antennae [31, 32]. Complex-type glycans without terminal galactose/fucose comprise the most abundant species in most (food) plants.…”
Section: Asn-linked Oligosaccharides In Plantsmentioning
confidence: 99%
“…On the other hand, peak e was not digested by this exoglycosidase, suggesting that GlcNAc residues might be replaced by other sugar molecules. Since 2D-sugar chain mapping analysis 17) and ESI-MS suggested that peaks d and peak e might harbor Lewis a epitopes like N-glycans linked to Jun a1 and Cry j1, two major cedar pollen allergens, 15,20) these sugar chains were treated with a mixture of 1-3/4 fucosidase and lacto Nbiosidase to confirm the occurrence of the Lewis a epitope unit (Gal1-3(Fuc1-4)GlcNAc1-). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1, N-glycan-containing fractions, indicated by a horizontal bar (elution time: 35-60 min), were pooled and evaporated to dryness. Since it has been found that almost all N-glycans linked to plant glycoproteins are eluted after M3FX on RP-HPLC, [13][14][15][18][19][20] the pooled fractions indicated by the bars were used for further structural analysis of Nglycans. After the pooled fractions were concentrated to dryness in vacuo, the resulting residue was dissolved in 20 mM Tris-HCl buffer, pH 7.8, containing 0.1 M NaCl, 5 mM CaCl 2 , and 5 mM MgCl 2 (5 ml), and put on a Con A-Sepharose 4B column (2:0 Â 25 cm) equilibrated with the same buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation